Yvon Lambert Actualité d'un bilan Paris 1972. - Lambert, Yvon; Claura, Michel (Paris : Yvon Lambert, 1972)
Andre, Carl ; Arakawa ; Askevold, David ; Barry, Robert ; Beckley, Bill ; Broodthaers, Marcel ; Buren, Daniel ; Christo ; Dezeuze, Daniel ; Dibbets, Jan ; Fulton, Hamish ; Huebler, Douglas ; Kawara, On ; Kienholz, Edward ; Lamelas, David ; LeWitt, Sol ; Long, Richard ; Mangold, Robert ; Marden, Brice ; Oppenheim, Dennis ; Renouf, Edda ; Ristori, François ; Ryman, Robert ; Salvo ; Sandback, Fred ; Toroni, Niele ; Tuttle, Richard ; Twombly, Cy ; Weiner, Lawrence
Yvon Lambert Actualité d'un bilan Paris 1972, Yvon Lambert, Paris, 1972
boek